2019
DOI: 10.18203/2349-3933.ijam20195664
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its different components in patients with acute coronary syndrome

Abstract: Background: Several components of the Metabolic Syndrome (MetS) are risk factor for cardiovascular diseases. So, this study was conducted to evaluate the prevalence of MetS and its components in patients with CAD.Methods: Author included all patients admitted with Acute Coronary Syndrome (ACS), who had CAD confirmed by coronary angiography. They were divided into two groups according to presence or absence of MetS based on International Diabetes Federation criteria. The prevalence of MetS and its individual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Sinha SK et al 17 reported mean age as 58.68 ± 5.6 years, with the preponderance of males (71.6%) in MS. However, contrasting findings were reported by Jain G et al 22 where metabolic syndrome was more prevalent in females (82.4%) than in male patients (57.6%) with ACS. Zaliunas R et al 23 reported prevalence of 70.2% and 52.6% MS in females and males respectively.…”
Section: Prevalence Of Metabolic Syndrome and Demographic Profilementioning
confidence: 61%
See 3 more Smart Citations
“…Sinha SK et al 17 reported mean age as 58.68 ± 5.6 years, with the preponderance of males (71.6%) in MS. However, contrasting findings were reported by Jain G et al 22 where metabolic syndrome was more prevalent in females (82.4%) than in male patients (57.6%) with ACS. Zaliunas R et al 23 reported prevalence of 70.2% and 52.6% MS in females and males respectively.…”
Section: Prevalence Of Metabolic Syndrome and Demographic Profilementioning
confidence: 61%
“…Jain G et al 22 reported patients with MS had hypertension (87.9%) as compared to non-hypertensive patients (12.1%), while 83.3% had diabetes mellitus. Sinha SK et al 17 reported the prevalence of the individual components of MetS as 47.5% abdominal obesity, 63.1% hypertension, 46.7% diabetes mellitus.…”
Section: Prevalence Of Various Components Of Metabolic Syndromementioning
confidence: 98%
See 2 more Smart Citations